OPTIMIZATION OF TENSILE STRENGTH AND PROCESSING TIME USING PCR-TOPSIS METHOD FOR FDM PROCESS - Lim, G.D.; Abd Latif, M.J.; Alkahari, M.R.; Yob, M.S.; Thapliyal, S.; Threemurty, L.R. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Fused Deposition Modeling (FDM) is widely applied in industries due to its cost efficiency and capability to fabricate complex geometrical part. However, the main issues in FDM technology are the fabricated part strength and printing time. Therefore, this study aims to examine the FDM printing parameter to obtain the optimum tensile strength and printing time. Three most important parameters of layer thickness, nozzle diameter and printing velocity were studied to assess the tensile strength and processing time. Taguchi and PCR-TOPSIS methods were employed to evaluate the multi-response optimization problem. The tensile strength of FDM printed specimen was determined according to ASTM D638 while the processing time was computed from slicing software. From the results, the optimal parameter setting was achieved at 1.0 mm nozzle diameter, 0.39 mm layer thickness and 50 mm/s printing velocity. In addition, printing velocity plays an important role toward the strength and printing time of FDM fabricated products followed by nozzle diameter and layer thickness.